Resilient Health Systems and National Security: Lessons from Kenya’s COVID-19 Response (National Security: A Journal of the National Defence University-Kenya, 2025)
The COVID-19 pandemic exposed critical vulnerabilities in both global and national health systems. It underscored the intricate relationship between public health and national security, emphasising the need for robust preparedness frameworks. This study examined how inefficiencies in the medical supply chain could impact Kenya's national security and public health preparedness, identified structural flaws that emerged during the crisis, and provided recommendations to enhance Kenya's preparedness. The study explains the existing structural gaps in the medical supply chain regime in the context of pandemic preparedness. It also examines the threats to Kenya’s health and national security arising from inefficiencies in the medical supply chain. Grounded in resilience theory, this study emphasises collaboration and building strong institutions for better service delivery. To provide well-informed recommendations, the study uses a qualitative approach. Using a case study design, the study draws on Kenya’s specific experiences during the pandemic to provide insights into strengthening national and regional strategies. The study utilised content analysis of documents, publications, and reports to obtain the relevant data. The study established that, whereas the country had a robust health supply chain capability before and during the COVID-19 pandemic, its reliance on global health supply chains during the pandemic exposed the country to health insecurity. It was also evident that for Kenya to be resilient, it must overcome local inefficiencies resulting in financial mismanagement and a lack of anticipatory resilience. It is also imperative for the country to leverage the potential of the East African Community (EAC) to build regional sufficiency. The findings aim to inform key stakeholders, including the Kenyan government’s public health organs.
Keywords: COVID-19, medical supply chain, national security, pandemic preparedness, public health emergencies